2016
DOI: 10.1371/journal.pone.0148563
|View full text |Cite
|
Sign up to set email alerts
|

Heavy Smoking Is More Strongly Associated with General Unhealthy Lifestyle than Obesity and Underweight

Abstract: BackgroundSmoking and obesity are major causes of non-communicable diseases. We investigated the associations of heavy smoking, obesity, and underweight with general lifestyle to infer which of these risk groups has the most unfavourable lifestyle.MethodsWe used data from the population-based cross-sectional Swiss Health Survey (5 rounds 1992–2012), comprising 85,575 individuals aged≥18 years. Height, weight, smoking, diet, alcohol intake and physical activity were self-reported. Multinomial logistic regressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(48 citation statements)
references
References 42 publications
0
46
0
2
Order By: Relevance
“…It has been suggested that tobacco use is related to unfavourable social and lifestyle behaviours in general . By contrast, the snus users investigated here were younger, more physically active, and had higher educational levels than both smokers and those who had never used tobacco, which may reduce their risk of diabetes.…”
Section: Discussionmentioning
confidence: 55%
“…It has been suggested that tobacco use is related to unfavourable social and lifestyle behaviours in general . By contrast, the snus users investigated here were younger, more physically active, and had higher educational levels than both smokers and those who had never used tobacco, which may reduce their risk of diabetes.…”
Section: Discussionmentioning
confidence: 55%
“…Um estudo recente identificou associação entre tabagismo e maus hábitos de EV 16 . Recomendou-se que medidas de prevenção ao tabagismo devem atentar à melhora do EV como um todo 16 .…”
Section: Introductionunclassified
“…Then, individuals were categorized into two groups: "heavy smokers" (more than 10 cigarettes/day) and "non-heavy smokers". 19 Alcohol consumption was assessed by asking whether the individual currently drank and how often. Then, the variable was categorized into two groups: "does not drink or drinks monthly" or "drinks daily or weekly".…”
Section: Individual Independent Variablesmentioning
confidence: 99%